Governance and Economic Growth - Gradstein, Mark (World Bank, Washington, DC, 2014)
Because protection of property rights cannot be appropriated by any individual, it is widely recognized as being the state's responsibility. Moreover, recent empirical evidence suggests that protection of property rights leads to higher investment levels and faster growth. The extent of property rights protection differs significantly across countries. The author integrates the emergence of property rights within a simple growth framework. Drawing on North (1990), he presents a model where economic performance and enforcement of property rights may reinforce each other. Initial conditions determine the economy's convergence to a high-income or a low-income steady state. Existing empirical evidence offers tentative support for this theory.